NURSERY RHYMES AS AN OBJECT OF STUDY IN LINGUOCULTUROLOGY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Linguoculturology can be said to have arisen exactly at the intersection of cultural studies and linguistics. Cultural studies (culturology) examine a person's awareness of themselves in social and cultural life in relation to nature, society, history, art, and other fields, whereas linguistics studies a person’s worldview as reflected and recorded in the mental models of the linguistic picture of the world. Nursey rhymes can be interpreted as an object of study in linguoculturology precisely because they embody diverse types of cultural information. Nursery rhymes have been passed down for centuries, refined over time, enriching their artistic, linguistic, human, and cultural features. These samples reflect a people’s ancient past, religious beliefs, daily life, and expectations for the future. Nursery rhymes reveals the fluency of children's speech, the richness of their imagination, their quick wit, and their affection toward their parents, loved ones, and life in general. In the following article discusses the formation of linguoculturology as a scientific discipline, its developmental stages, and the interpretation of nursery rhymes as an object of research.